2016
DOI: 10.3389/fmicb.2016.01286
|View full text |Cite
|
Sign up to set email alerts
|

Salicornia strobilacea (Synonym of Halocnemum strobilaceum) Grown under Different Tidal Regimes Selects Rhizosphere Bacteria Capable of Promoting Plant Growth

Abstract: Halophytes classified under the common name of salicornia colonize salty and coastal environments across tidal inundation gradients. To unravel the role of tide-related regimes on the structure and functionality of root associated bacteria, the rhizospheric soil of Salicornia strobilacea (synonym of Halocnemum strobilaceum) plants was studied in a tidal zone of the coastline of Southern Tunisia. Although total counts of cultivable bacteria did not change in the rhizosphere of plants grown along a tidal gradien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 76 publications
(107 reference statements)
4
31
0
Order By: Relevance
“…Coastal ecosystems are subjected to cyclic shifts of different environmental conditions such as nutrient availability and salinity and oxygen concentrations in the soil and sediments (Alongi, 1988;Mitra et al, 2008). The importance of plant growth promoting (PGP) bacteria in coastal ecosystems was largely reported (Gontia et al, 2011;Jha et al, 2012;Mapelli et al, 2013;Marasco et al, 2016;Mesa et al, 2015;Siddikee, 2010), as well as the influence of the tidal regime on the selection of specific bacterial assemblages in the root systems (Marasco et al, 2016;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Coastal ecosystems are subjected to cyclic shifts of different environmental conditions such as nutrient availability and salinity and oxygen concentrations in the soil and sediments (Alongi, 1988;Mitra et al, 2008). The importance of plant growth promoting (PGP) bacteria in coastal ecosystems was largely reported (Gontia et al, 2011;Jha et al, 2012;Mapelli et al, 2013;Marasco et al, 2016;Mesa et al, 2015;Siddikee, 2010), as well as the influence of the tidal regime on the selection of specific bacterial assemblages in the root systems (Marasco et al, 2016;Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In arid environments, desert farming favours the selection of drought‐protecting microbial assemblages (Marasco et al ., ; TerHorst et al ., ; Soussi et al ., ) that are enriched and rearranged in the plant rhizosphere and endosphere (Mapelli et al ., ; Marasco et al ., ; ; Cherif et al ., ; Ferjani et al ., ; Santos‐Medellín et al ., ). PGP microorganisms use several mechanisms to stimulate drought tolerance in plants (Vurukonda et al ., ; Etesami and Maheshwari, ): (i) the microbial enzyme 1‐aminocyclopropane‐1‐carboxylate (ACC) deaminase contributes to control the concentration of the plant stress phytohormone ethylene, by degrading its precursor ACC (Glick, ); (ii) microorganisms contribute to modulate plant hormone homeostasis by producing auxin [i.e., indole‐3‐acetic acid (IAA)], cytokinins and giberellins.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have suggested that the habitat-adapted symbiotic microorganisms associated with plants growing in harsh environments might help these host plants tolerate abiotic stresses (22)(23)(24). Recently, halophyte-associated endophytes and rhizosphere microorganisms have been shown to increase the salt tolerance of the host plants (25)(26)(27)(28). However, few details of halophyte microbiota composition are available, and the mechanisms by which halophyte-associated microbes increase salinity tolerance in halophytes remain unclear.…”
mentioning
confidence: 99%